Nutritional problems in rheumatoid arthritis patients with temporomandibular joint involvement - Manolya Ilhanli; Ilker Ilhanli (Exploration of Musculoskeletal Diseases, 2023)
Rheumatoid arthritis (RA) is an inflammatory arthritis that affects synovial joints, and it is not surprising that the temporomandibular joint (TMJ), a synovial joint, is also affected. However, TMJ is rarely the first affected joint in the course of RA. Often, RA patients come to the physician with more focus on complaints in other peripheral joints. Therefore, asking TMJ complaints and symptoms, and TMJ examination in RA patients is often neglected by doctors too, because they focus more on other joints. This neglect may cause serious damage to the joints and cause disability. Examination of TMJs, which is a crucial component of vital activities such as nutrition and speech, should be added to the routine. Also, further studies may be focused on adding TMJ assessment to disease activity scales and health assessment questionnaires.